An evaluation of the generalized–α time integration scheme for a transient response of nonlinear structures. (1st February 2020) - Lozina, Zeljan; Sedlar, Damir; Bartulovic, Andela
Highlights: Independent and innovative evaluation of the new KDP generalized- α time integration scheme has been performed. Energy and momentum conservation and frequency resolution have been adopted as quality criteria. A number of indicative nonlinear benchmark involving different types of nonlinearity is introduced. Abstract: The recently developed promising generalized– α time integration scheme for nonlinear structures is evaluated and compared with Bathe scheme. The nonlinear benchmarks are developed and implemented in order to assess reliability and numerical efficiency of the schemes. Both schemes proved to be comparably efficient and accurate while Bathe method has higher frequency resolution. A practical application of the considered schemes to the nonlinear cable structure problem that support conclusions is supplied.